I know this much is true - Lamb, Wally (New York, NY : Regan Books, 1998)
Dominick Birdsey, a forty-year-old housepainter living in Three Rivers, Connecticut, finds his subdued life greatly disturbed when his identical twin brother Thomas, a paranoid schizophrenic, commits a shocking act of self- mutilation.
Includes bibliographical refences.
Accelerated Reader AR
Keywords: Italian Americans -- New England -- Fiction; Fathers and sons -- New England -- Fiction; Mentally ill -- New England -- Fiction; Brothers -- New England -- Fiction; Twins -- New England -- Fiction; Schizophrenia -- Fiction; New England -- Fiction; Psychological fiction; Domestic fiction